DIVERSITY OF LAURACEAE FAMILY IN HON BA NATURE RESERVE, KHANH HOA PROVINCE - Van Hop, Nguyen; Manh Hung, Bui; Quoc Trong, Huynh (Journal of Forestry Science and Technology, 2020)
Lauraceae is a big plant family, distributed in the tropical and subtropical, including many different life-forms, mainly timber trees, and shrubs. This family has many important values not only for biodiversity but also for economic, ecological and conservation values. However, in Vietnam in general and Hon Ba Nature Reserve, Khanh Hoa province in particular, there is very little research on Lauraceae family. Therefore, an assessment of the plant resource of the Lauraceae family was carried out. In this study seven survey transects, 22 plots with an area of 1000 m2 (25 x 40 m) passing seven elevation belts, four different forest status was established to clarify the diversity of species composition, life-form spectrum, geographical factors, use-value, conservation status, species diversity by elevation belt and forest status. The results showed that 28 species, nine genera, which add a genus, seven species were found for this area. There are three plant species of threatened were listed in Vietnam Red Data Book (2007) and two species of group IIA of Decree No.32/2006/ND-CP of the Government. The life-form spectrum of Lauraceae family was determined as SB = 28.57Mg + 28.57Me + 17.86Mi + 10.71Na + 14.28Pp. Three major geographical factors were recorded, in which the endemic factor is the most abundant with 19 species (67.86%). Among the four groups of used value, the group for timber is dominant with 44.07%, the lowest is medicine with 10.17%. The Lauraceae family distributed mainly at the elevation belt of 401 - 600 m with seven genera, 26 species (35.13%). At IIA status has a most diverse number of species with 11/28 species.